HUBUNGAN PAPARAN INFODEMIC COVID-19 TERHADAP KEPATUHAN PENERAPAN PROTOKOL KESEHATAN PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Ni Made Kadek Artini; Desak Putu Yuli Kurniati (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2023)
The outbreak of the coronavirus has had an impact on people's lives. COVID-19 not only has an impact on health but also on the economy, education, social and security. A lot of COVID-19 hoax information circulating on social media can confuse the public (infodemic). Infodemic leads to excessive information related to COVID-19 that can interfere with finding solutions and not necessarily valid information content. This study aims to determine the relationship between exposure to COVID-19 infodemic and compliance with the application of health protocols in Udayana University Medical Faculty students. This research is a quantitative analytic study with a cross sectional study approach which obtained 236 respondents. Based on the results of the study, most of the women (70.34%), reside in Denpasar (33.90%), the PSSKPD study program (38.56%) and the 2019 batch (53.81%). In addition, respondents also access information well through social media (94.07%), have a positive attitude in receiving COVID-19 information (69.92%), have a positive perception of COVID-19 information (67.37%) so that respondents were not exposed to COVID-19 hoaxes (58.47%) and respondents were obedient in implementing health procedures (75%). In this study, gender characteristics had a relationship with health care adherence (p=0.002). Likewise, access to information (p=0.026) and perception of COVID-19 information (p=0.045) had a relationship with health care compliance. Therefore, it is expected to use FK's social media to provide positive information, especially regarding COVID-19 and urge students to follow all FK's social media. Keyword : Coronavirus, Infodemic, Health Protocol